(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Metazoans typically have a single-celled stage in the life cycle, a sexually produced zygote or apomictically produced asexual propagule. Some metazoans have vegetative reproduction, in which new individuals are formed from a large number of cells. Two families of scale insects, Pseudococcidae and Diaspididae, are apparently unique among Metazoa in that each individual is founded by two genomically distinct cells. One of these cells is a normal diploid zygote formed from fusion of ovum and sperm; it gives rise to the germline and most of the soma. The other cell is a polyploid secondary zygote, typically a pentaploid product of the fusion of the first (2N) and second (1N) polar bodies with a cleavage nucleus derived from the first zygote (2N). The secondary zygote gives rise to a specialised somatic tissue, the bacteriome. which houses vertically transmitted endosymbiotic bacteria. The bacteriome is analogous to endosperm in that it is a polyploid nutritive tissue with an enriched maternal genomic contribution, but differs in that it remains an integral and active part of the organism (at least in females) throughout ontogeny. Especially given the prevalence of brooding, and sex determination by paternal genome elimination in males, there is enormous scope for intragenomic conflict in these insects, especially over the sex ratio. Consistent with the conflict hypothesis there is considerable variation in genomic composition of the bacteriome between species.